Literary theory : an anthology - Rivkin, Julie; Ryan, Michael, 1951- (Blackwell Pub., 2004)
Literary Theory: An Anthology is a definitive collection of classic and contemporary statements in the field of literary theory and criticism. It is an invaluable resource for students who wish to familiarize themselves with the most recent developments in literary theory and with the traditions from which these new theories are derived. The anthology represents all the major schools and methods that make up the dynamic field of literary theory. It contains classic texts from a range of movements, including Formalism, Structuralism, Marxism, Psychoanalysis, Deconstruction, Historicism, and Feminism, and incorporates cutting-edge work by leading theoreticians in the fields of Postmodernism, Cultural Studies, Post-colonialism, Gay and Lesbian studies, and Ethnic Studies. For the second edition, the content has been updated to include the most recent influential texts, particularly in the areas of Ethnic Studies, Transnational Studies, and Cultural Studies.